Peran FKUB dalam Mewujudkan Toleransi Antar Umat Beragama di Kota Bandar Lampung - Afni Rahmayanti; Dela Astarika; Ahmad Amri; Abdul Syukur; Sonhaji; Rika Damayanti (LPPM Politeknik Piksi Ganesha, 2025)
Abstract: This study aims to understand how community development in Bandar Lampung City is implemented within the context of interreligious tolerance. As a multicultural city characterized by religious, ethnic, and cultural diversity, Bandar Lampung represents a dynamic social space for building interfaith harmony. This research employs a qualitative descriptive approach, utilizing in-depth interviews, participatory observations, and documentation involving religious leaders, members of the Interreligious Harmony Forum (FKUB), local government officials, and interfaith community members. The findings reveal that community development based on tolerance is realized through the synergy between government institutions, religious figures, social organizations, and the public in activities such as interfaith dialogues, joint social services, and multicultural education programs in schools. The FKUB plays a pivotal role as a mediator and facilitator in maintaining social stability and resolving religious issues peacefully. However, challenges such as digital disinformation, radicalism, and the weakness of tolerance education still hinder the creation of a conducive social environment. Therefore, strengthening digital literacy, enhancing institutional capacity, and integrating character education based on tolerance are strategic steps toward achieving harmonious, inclusive, and sustainable community development in Bandar Lampung City. Abstrak: Penelitian ini bertujuan untuk memahami bagaimana pembangunan masyarakat di Kota Bandar Lampung diimplementasikan dalam konteks toleransi antar umat beragama. Kota Bandar Lampung sebagai wilayah multikultural dengan keragaman agama, etnis, dan budaya menjadi ruang sosial yang dinamis dalam membangun harmoni kehidupan keagamaan. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, melalui wawancara mendalam, observasi partisipatif, dan dokumentasi terhadap tokoh agama, pengurus Forum Kerukunan Umat Beragama (FKUB), pemerintah daerah, serta masyarakat lintas agama. Hasil penelitian menunjukkan bahwa pembangunan masyarakat berbasis toleransi diwujudkan melalui sinergi antara pemerintah, tokoh agama, lembaga sosial, dan masyarakat dalam kegiatan seperti dialog lintas iman, bakti sosial bersama, serta pendidikan multikultural di sekolah. FKUB berperan penting sebagai mediator dan fasilitator dalam menjaga stabilitas sosial dan menyelesaikan persoalan keagamaan secara damai. Namun demikian, tantangan seperti pengaruh disinformasi digital, radikalisme, dan lemahnya pendidikan toleransi masih menjadi penghambat terciptanya lingkungan sosial yang kondusif. Oleh karena itu, penguatan literasi digital, peningkatan kapasitas kelembagaan, serta integrasi pendidikan karakter berbasis toleransi menjadi langkah strategis dalam mewujudkan pembangunan masyarakat yang harmonis, inklusif, dan berkelanjutan di Kota Bandar Lampung.